Social Studies Learning in Elementary School Reveals Effective Teaching Strategies - mardianti, Sri; Nurmayanti, Nurmayanti; Syafruddin, Syafruddin (JUPE : Jurnal Pendidikan Mandala, 2024)
It is very important for children to learn social studies in elementary school. This is evidenced by the fact that there are still students who do not fully understand all the material taught in social studies class. In the era of Revolution 4.0, educators are expected to help students think criticallytowards social problems and respond creatively to matters related to social life. Educators can encourage students to discuss and work together to overcome social problems. Social studies lessons at the elementary school level must be delivered to students in a constructivist manner. There are five methods that can be taught in social studies classes, including collaboration-based learning, design-based learning, inquiry-based learning, pembelajaran berbasis proyek, dan pembelajaran berbasis masalah. Metodologi yang digunakan dalam penelitian ini adalah tinjauan literatur terhadap artikel.